Wet milling synthesis of ammonium cobalt phosphate hydrate platelets for LCP‐olivine cathodes of LIBs using a bead mill. Issue 2 (9th August 2022) - Kondo, Akira; Kozawa, Takahiro; Ishii, Toshihiro; Naito, Makio
Abstract: In this study, NH4 CoPO4 ·H2 O (ACP) platelets were synthesized from NH4 H2 PO4 and Co(OH)2 by wet milling process using a bead mill. ACP is one of the precursors of LiCoPO4 (LCP) cathode materials for Li‐ion batteries. In the wet milling, ACP large platelets were synthesized in a short time at the beginning, and the large platelets were gradually cleaved into the smaller platelets. The lateral sizes of the ACP platelets were several 10 μm at 30 min and about 10 μm at 5 h. It was found that the ACP platelets were synthesized efficiently by using the bead mill as a promising machine for the scale‐up in manufacturing. The ACP platelets were converted into LCP by mixing with Li2 CO3 and heating, whereas platelet shapes were retained. The initial discharge capacities of the cathodes using the LCP platelets converted from the ACP of 30 min and 5 h milling were 70 and 95 mAh/g at 0.05 C, respectively. It is because the specific surface area of the latter sample (3.3 m 2 /g) was larger than that of the former (2.2 m 2 /g). The larger specific surface area possibly led to the increase of contacts with electron conductive additives (carbon) and electrolytes.